Effects of 3-Dimensional Computer Simulation Secondary School Students’ Academic Achievement in Chemistry - Iyabode Nike Ojelade; C G Ekpo; Busayo Gbemisola Aregbesola (Journal of Science and Science Education, 2021)
The study investigated the effect of 3-Dimensional Computer Simulation on Secondary School Students’ Academic Achievement in Chemistry, Ibadan Oyo State. Two research questions and two hypotheses were raised to guide the study. The study adopted pre-test, post-test non-randomized control group design quasi experimental design. The total population of the study comprised of all the 70,843 SSII chemistry students in Ibadan, Oyo State. A simple random sampling technique, using balloting without replacement was used to select two intact classes from the forty-two public secondary schools of mixed gender in the two Local Government Areas. The two schools selected constituted 127 students, 62 students (37 males and 25 females and convention group comprised of 65 students (35 male and 30 female). Two instruments were used to collect data in the study: Chemistry Achievement Test (CAT) and Chemistry Retention Test (CRT) with the reliability coefficients of 0.86 and 0.87 respectively using Kuder Richardson 21 (KR-21). Data were analyzed using mean and standard deviation were used to answer the research questions while t-Test was used to test the null hypotheses. Findings revealed that there was significant difference in the mean achievement score of secondary school students taught chemistry using 3-D computer simulation and their counterparts in control group. There was no significant difference in the mean achievement score of male and female students taught chemistry using 3D-computer simulation. These implied that 3-D computer simulation can be used to enhance students’ academic achievement in chemistry. It was therefore recommended among others that 3-D computer simulation strategy (3-DCS) was found effective in improving students’ academic achievement. Therefore. It can be recommended that curriculum planner can integrate this strategy as one of the strategies recommended for use by chemistry teachers in the curriculum.